Penggunaan Media Sosial dalam Penyuluhan Anti Korupsi Bagi Pemuda Desa Jati Mulyo Kecamatan Jati Agung Kabupaten Lampung Selatan - Sri Furyani; Ahmad Syarifudin; Shely Nasya Putri; Muh. Munif Jazuli; Lisa Safitri; Farida; Dini Lionita Septiani (Nuban Jaggadhita Center, 2023)
This community service activity aims to provide an understanding to the youth of Jati Mulyo Village regarding the use of social media in anti-corruption advocacy. Through social media, the village youth will actively participate in combating criminal activities through anti-corruption campaigns. The objective of this activity is to foster awareness and consciousness about the dangers and anti-corruption behavior among the youth today. Consequently, they can alter their perceptions and attitudes towards corruption and actively resist it. The method employed in this community service is Participatory Action Research (PAR), which has enhanced knowledge and understanding regarding the use of social media in anti-corruption education among the village youth. The outcomes of this service show that the youth in Jati Mulyo Village have effectively absorbed the knowledge and can formulate anti-corruption campaigns through social media that are compliant with the law..